Analisis Likuiditas, Profitabilitas, dan Rasio Aktivitas terhadap Harga Saham pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2020-2024 - Ni Kadek Febriani; I Dewa Nyoman Usadha; I Putu Budhiyasa (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Stock prices represent the market’s consensus regarding the fair value of a business entity, formed through a rational assessment of both financial and non-financial information. Within the frameworks of signaling theory and market efficiency, financial ratios serve as fundamental indicators reflecting a company's ability to generate profit, manage assets, and maintain short-term liquidity stability. When the market faces systemic disruptions, such as the COVID-19 pandemic, and transitions toward post-pandemic normalization, investor sensitivity to internal indicators tends to increase due to heightened external uncertainty. Consequently, a deep understanding of the internal determinants of stock prices becomes increasingly critical for data-driven investment decision-making. This study aims to empirically examine the effect of the Current Ratio (CR), Return on Assets (ROA), and Total Asset Turnover (TATO) on stock prices, both partially and simultaneously, in companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. A quantitative approach was employed, using a descriptive-verificative design and secondary data drawn from audited financial statements and annual closing stock prices. The sample consisted of 91 companies selected through purposive sampling, and the data were analyzed using multiple linear regression with SPSS version 27. The analysis results indicate that all three independent variables have a positive and significant impact on stock prices, both individually and collectively. This study contributes to the capital market literature by highlighting the relevance of financial ratios in explaining stock price fluctuations in the post-pandemic period, a topic that remains underexplored in the context of developing countries.